AINI - embodied conversation agent applicable for interactive games - Goh, Ong Sing; Fung, C.C. (WSEAS Press, 2008)
Recent advances in Natural Language Processing (NLP) and Artificial Intelligence (AI) in general have advances this field in realizing the vision of a more humanoid interactive system with embodied conversation agent (ECA). This paper presented our development of the ECA called Artificial Intelligent Natural-language Identity or AINI. In this paper, we also present and discuss the use of such ECA for inclusion in interactive games. We present the technical design of our ECA and its performance.